Kepemimpinan Guru Pendidikan Agama Islam Dalam Mengembangkan Budaya Islami Di SMPN 3 Selong - Nurul Jum'ah Fathi Huballoh; Ari Suandi (Jurnal Ilmu Pendidikan, 2026)
The leadership of Islamic education teachers plays a very strategic role in instilling Islamic values. Islamic culture in schools becomes an important foundation in shaping students' character and morals amid the challenges of the modern era. Islamic Education teachers, as leaders in developing Islamic culture, have responsibilities for all aspects of life, from responsibilities in classroom learning processes to activities outside the classroom or school environment. This type of research is qualitative research using qualitative descriptive analysis, where data collection techniques are through observation, interviews, and documentation. The data analysis method consists of data collection, data reduction, data presentation, and drawing conclusions. The research results show that the leadership of Islamic religious education teachers is realized through three main functions: 1) Innovator, initiating programs to habituate students in several activities, including: reading the Qur'an every morning before learning begins, Dhuha prayer, congregational Dhuhr prayer, Friday activities such as reading Surah Yasin and delivering short sermons, and commemorating the Prophet's birthday. 2) Role Model, the teacher becomes a model of moral discipline in worship and polite speech that students emulate, encouraging good habits, enforcing discipline, providing motivation, giving rewards, and giving punishments to students who break the rules. 3) The PAI teacher's leadership model in developing an Islamic culture is a democratic leadership model that collaborates with all teachers in the institution. Overall, the leadership of PAI teachers significantly contributes to creating a school culture that is religious, safe, and conducive to students' moral development.